Some Inverse Relations Determined by Catalan Matrices. (24th September 2013) - Yang, Sheng-liang
Abstract : We use theA -sequence andZ -sequence of Riordan array to characterize the inverse relation associated with the Riordan array. We apply this result to prove some combinatorial identities involving Catalan matrices and binomial coefficients. Some matrix identities obtained by Shapiro and Radoux are all special cases of our identity. In addition, a unified form of Catalan matrices is introduced.